Jura og kirkelove : Anders Sandøe Ørsteds rummelige opfattelse under den sene enevælde - Rasmussen, Jens (Kirkehistoriske Samlinger, 2023)
The young jurist and office-holder at the turn of the nineteenth century, A.S. Ørsted, was very interested in I. Kant’s moral law. Gradually, he reached the conclusion that separates Kant’s moral law from an objective judicial system. The individual’s moral conscience was the subjective basis for the judicial system. A.S. Ørsted built on contemporary ideas of moral and religious traditions. Looking ahead of a rigidly doctrinal approach, he would watch for the teachings of everyday life. Jurisprudence gains from Ørsted’s merits as the link between life and the legal system became a basic principle for A.S. Ørsted in his legislative work as an official authority of ecclesiastical laws during late absolutism. Ørsted’s views on a State Church ensuring broadness was shared by bishop J.P. Mynster. Ørsted’s religious tolerance was of great importance for his ideas on a spiritual interpretation of the obligation of pastoral oath on the Bible, on confessions, and on applicable regulationssuch asrituals. Ørsted’s attitude towardsthe Danish Chancellery’s handling of a revision of the ritual case shows his tolerance in religious complaints. It becomes even more visible in his wish to avoid baptize by force of the Baptists’ children. Jurisdictional authority should make legal decisions on the background of respect for life in a particular situation and protect and defend every Christian subject. In spiritual religious matters it involved tolerance and freedom of conscience.